Are There Differences in the Management of Acute Pancreatitis Cases Due to Severe Hypertriglyceridemia in Pregnant Women? - Kilinc, Faruk; Senates, Ebubekir; Demircan, Fatih; Pekkolay, Zafer; Gozel, Nevzat; Guven, Mehmet; Tuzcu, Alpaslan Kemal (Int Scientific Literature, Inc, 2018)
Background: The aim of this study was to determine the prognosis of severe disease and treatment approaches of both normal and pregnant, especially in patients with severe pancreatitis due to hypertriglyceridemia. Material/Methods: We included 30 patients (20 females and 10 males) in this study whose follow-ups and treatments were per- formed after a diagnosis of hypertriglyceridemia-induced acute pancreatitis between January 2011 and May 2017. Patient personal information, such as age, sex, pre-treatment and post-treatment triglyceride levels, receipt of anti-hyperlipidemic treatments or plasmapheresis, and family history, were collected from hospital records and patient files. Patients with severe pancreatitis history, score, and prognosis were included to increase the value of our study. Mild and moderate cases were excluded. Results: The mean age of the patients was 35 +/- 6 years. Twenty-four patients (80%) received an anti-hyperlipidemic treatment before their pancreatitis attacks. Plasmapheresis was performed on 8 patients before their pancreatitis attacks. Eighteen patients (60%) had a family history suggesting familial hypertriglyceridemia. Twelve patients (40%) were pregnant. Conclusions: The treatment of hypertriglyceridemia-induced acute pancreatitis was mostly confined to supportive, palliative treatments. However, plasmapheresis is a possible treatment option and should be used in the early stages of this disease. The response to medical treatment and support treatment was better in pregnant patients than in the other patient group, and pregnant patients did not require plasmapheresis.
Keywords: Hypertriglyceridemia; Pancreatitis; Pregnant Women